PJMHS 2021
DOI: 10.53350/pjmhs211582508
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Covid-19 Pandemic on the Early Trimester Pregnancies

Abstract: Background and Aim: The COVID-19 pandemic caused by severe acute respiratory syndrome (SAR-CoV-2) had severe consequences and complications on the global health care system. Recent medical studies have been focused on the effect of COVID-19 pandemic on pregnancies outcomes especially early pregnancies. The present study aimed to investigate the impacts of the COVID-19 pandemic early-trimester pregnancies. Materials and Methods: This retrospective study was carried out on 76 women who visited Obstetrics and Gyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…According to a study by Khosa et al, their reported cases (n = 76) with COVID-19 either miscarried in the first trimester or proceeded through the gestation with intrauterine growth restriction (IUGR) being evident in the second and third trimesters [24]. The results from a UK meta-analysis (n = 3545 women) support the hypothesis that the earlytrimester pregnancy loss rate is affected by COVID-19 infection, and pregnant women with COVID-19 have a higher risk of miscarriage [25].…”
Section: Miscarriage Rates and Covid-19 Infectionmentioning
confidence: 99%
“…According to a study by Khosa et al, their reported cases (n = 76) with COVID-19 either miscarried in the first trimester or proceeded through the gestation with intrauterine growth restriction (IUGR) being evident in the second and third trimesters [24]. The results from a UK meta-analysis (n = 3545 women) support the hypothesis that the earlytrimester pregnancy loss rate is affected by COVID-19 infection, and pregnant women with COVID-19 have a higher risk of miscarriage [25].…”
Section: Miscarriage Rates and Covid-19 Infectionmentioning
confidence: 99%